2005
DOI: 10.1007/s00464-005-0367-3
|View full text |Cite
|
Sign up to set email alerts
|

Immediate peritoneal response to bacterial contamination during laparoscopic surgery

Abstract: Despite a transient impairment of the immediate peritoneal response to a septic challenge, the degree of injury with LS is lower than that with open surgery, and abdominal infection can therefore be better controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
0
14
0
2
Order By: Relevance
“…The normal peritoneal cavity contains less than 100 ml of serous fluid, which is essentially an ultrafiltrate of plasma with a protein concentration less than 3 g/dl. [21] The peritoneum usually contains fewer than 300 cells/mm 3 , mostly macrophages, some desquamated mesothelial cells and lymphocytes. Peritoneal macrophages are integral to the primary inflammatory response generated in the abdominal cavity in response to infection and cancer.…”
Section: Peritoneum;mentioning
confidence: 99%
See 2 more Smart Citations
“…The normal peritoneal cavity contains less than 100 ml of serous fluid, which is essentially an ultrafiltrate of plasma with a protein concentration less than 3 g/dl. [21] The peritoneum usually contains fewer than 300 cells/mm 3 , mostly macrophages, some desquamated mesothelial cells and lymphocytes. Peritoneal macrophages are integral to the primary inflammatory response generated in the abdominal cavity in response to infection and cancer.…”
Section: Peritoneum;mentioning
confidence: 99%
“…[1,2] Laparoscopic surgery (LS) has become a valuable tool in general surgery following the success of laparoscopic cholecystectomy which has many advantages over the conventional cholecystectomy. [3] The use of minimally invasive techniques have been shown to decrease the postoperative pain, causing less sympathetic response leading to less postoperative ileus, decreased respiratory distress, diminished hospital stay and more rapid return to preoperative physical activities. [3,4] Studies have shown that LS minimizes the surgical trauma, as demonstrated by the diminished release of acute inflammatory markers, fast return of cytokine levels to normal values and lower cortisol levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inwieweit sich dieser Effekt auch auf die Immunkompetenz des Peritoneums übertragen lässt, ist unklar. Targarona et al [7] konnten aufzeigen, dass der Einsatz der Laparoskopie zu einer besseren immunologischen Kontrolle des septischen Fokus führt, und dies trotz einer vorübergehenden Reduktion der Immunkompetenz. In zahlreichen weiteren Studien konnte über dies hinaus demonstriert werden, dass der Einsatz der Laparoskopie die Immunkompetenz des Organismus besser erhält [8,9].…”
Section: Pathophysiologische üBerlegungen Und Gründe Für Das Laparoskunclassified
“…There is experimental evidence that pneumoperitoneum predisposes to bacterial translocation and increases the systemic inflammatory response (Bloechle et al, 1998), but other studies have not confirmed this finding (Gurtner et al, 1995;Wichterman et al, 1979). In a model of peritonitis induced by bacterial inoculation in rats subjected to laparoscopy, elevation of the abdominal wall and laparotomy, the changes of the peritoneal immune system in response to the abdominal infection were lower in the group treated by laparoscopy (Targarona et al, 2006). In a similar study, the number of bacterial colonies obtained in the peritoneal fluid, the rates of positive blood cultures and the peritoneal levels of IL-1 and IL-6 were significantly lower after 24 and 72 hs in the groups subjected to laparoscopy.…”
Section: Introductionmentioning
confidence: 98%